Emotion Analysis in Narcotics Video MINORIS Music on Public Service Advertisement Video Provincial Prosecutor’s Office Kepulauan Riau - Nur Cahyono, Yusuf Rizky; Prasetiya, Happy Yugo; Adam, Chairoel; Saputra, Aldino (Jurnal Pendidikan Multimedia (Edsence), 2024)
Minoris music is a musical composition created as a means of conveying messages to viewers who see a public service advertisement video with the title narcotics video. Minoris music is music that aims to make the audience feel the message that the narcotics video wants to convey. Minoris' music is an accompaniment to a socialisation video with a narcotics theme that is socialisation in nature. This socialisation is more specifically targeted at the world of education from elementary, middle, high school, to university levels. In the application of a method, the research used is, using a qualitative way The use of research in a qualitative way is a research concept that aims as a process of understanding the subjects to be obtained from research. For example behaviour, motivation, action and perception. The method is carried out thoroughly and uses the description method, in determining the right words and language according to the natural context. In revealing the context aspect in the application of the analysis of Minoris Music, the author uses the basis of the analysis of Music Cultures of The Pacific, The Near East and Asia, which includes aspects of time, and also the theory of tone, tempo as a reference that minoris music is able to play emotions in the socialisation video of public service advertisements. The result of the research is that minoris music can bring emotions in the public service advertisement video of the Riau Islands Provincial Prosecutor’s Office  using DAW Studio One. In its application is the application of Tempo and Minor Basic Tone used in the manufacturing process. In its application, the author will only analyse the musical relationships that cause influence in the aspect of Minoris music in the application of the Socialisation Video with the theme of narcotics.